The PRETTY FEW SEEDS2 gene encodes an Arabidopsis homeodomain protein that regulates ovule development. - Park, SO; Zheng, Z.; Oppenheimer, DG; Hauser, BA.
The PRETTY FEW SEEDS2 gene encodes a homeodomain protein that regulates ovule development. In peptide alignments spanning the homeodomain and the WOX domain, PFS2 shared 95